Hymenolepis nana: a case report of an intestinal helminthic infection from Northern India - Sangeeta Singh; Manodeep Sen; Nikhil Raj; Riddhi Singh; Jyotsna Agarwal (MGM Journal of Medical Sciences)
Hymenolepis nana (H. nana), known as the dwarf tapeworm, is an intestinal helminth. This report highlights a case of H. nana infection in a young female from Northern India who presented with abdominal pain and achieved a favorable outcome following antiparasitic treatment. An 18-year-old female from a rural community in Kothara village, Baharaich, Uttar Pradesh, India, was diagnosed with H. nana infection. She exhibited mild iron deficiency anemia and granulocytosis but remained largely asymptomatic despite a moderate infection burden. While H. nana infections are often asymptomatic, prompt treatment is essential. Without intervention, the infection can spread within isolated rural populations. Therefore, incorporating H. nana screening into routine evaluations for intestinal parasites and treating even asymptomatic cases is vital to prevent further transmission.